ECP versus ruxolitinib in steroid-refractory acute GVHD - a retrospective study by the EBMT transplant complications working party: original article - Penack, Olaf; Peczynski, Christophe; Boreland, William; Lemaitre, Jessica; Afanasyeva, Ksenia; Kornblit, Brian; Jurado, Manuel; Martinez, Carmen; Natale, Annalisa; Pérez-Simón, Jose Antonio; Brunello, Lucia; Avenoso, Daniele; et al. (Frontiers in immunology, 2023)
Introduction: Extracorporal Photophoresis (ECP) is in clinical use for steroid-refractory and steroid-dependent acute GVHD (SR-aGVHD). Based on recent Phase-III study results, ruxolitinib has become the new standard of care for SR-aGVHD. Our aim was to collect comparative data between ruxolitinib and ECP in SR-aGVHD in order to improve the evidence base for clinical decision making. Methods: We asked EBMT centers if they were willing to participate in this study by completing a data form (Med-C) with detailed information on GVHD grading, -therapy, -dosing, -response and complications for each included patient. Results: 31 centers responded positively (14%) and we included all patients receiving alloSCT between 1/2017-7/2019 and treated with ECP or ruxolitinib for SR-aGVHD grades II-IV from these centers. We identified 53 and 40 patients with grades II-IV SR-aGVHD who were treated with ECP and ruxolitinib, respectively. We performed multivariate analyses adjusted on grading and type of SR-aGVHD (steroid dependent vs. refractory). At day+90 after initiation of treatment for SR-aGVHD we found no statistically significant differences in overall response. The odds ratio in the ruxolitinib group to achieve overall response vs. the ECP group was 1.13 (95% CI = [0.41; 3.22], p = 0.81). In line, we detected no statistically significant differences in overall survival, progression-free survival, non-relapse mortality and relapse incidence. Discussion: The clinical significance is limited by the retrospective study design and the current data can’t replace prospective studies on ECP in SR-aGVHD. However, the present results contribute to the accumulating evidence on ECP as an effective treatment option in SR-aGVHD.
Gesehen am 16.04.2024